Nuclear translocation of PKC‐ α is associated with cell cycle arrest and erythroid differentiation in myelodysplastic syndromes (MDSs). Issue 2 (4th January 2018) - Poli, Alessandro; Ratti, Stefano; Finelli, Carlo; Mongiorgi, Sara; Clissa, Cristina; Lonetti, Annalisa; Cappellini, Alessandra; Catozzi, Alessia; Barraco, Marilena; Suh, Pann‐Ghill; Manzoli, Lucia; McCubrey, James A.; et al.
Abstract : PI‐PLCβ1 is involved in cell proliferation, differentiation, and myelodysplastic syndrome (MDS) pathogenesis. Moreover, the increased activity of PI‐PLCβ1 reduces the expression of PKC‐α, which, in turn, delays the cell proliferation and is linked to erythropoiesis. Lenalidomide is currently used in low‐risk patients with MDS and del (5q), where it can suppress the del(5q) clone and restore normal erythropoiesis. In this study, we analyzed the effect of lenalidomide on 16 patients with low‐risk del(5q) MDS, as well as del(5q) and non‐del(5q) hematopoietic cell lines, mainly focusing on erythropoiesis, cell cycle, and PI‐PLCβ1/PKC‐a signaling. Overall, 11 patients were evaluated clinically, and 10 (90%) had favorable responses; the remaining case had a stable disease. At a molecular level, both responder patients and del(5q) cells showed a specific induction of erythropoiesis, with a reduced γ /β‐globin ratio, an increase in glycophorin A, and a nuclear translocation of PKC‐α. Moreover, lenalidomide could induce a selective G0 /G1 arrest of the cell cycle in del(5q) cells, slowing down the rate proliferation in those cells. Altogether, our results could not only better explain the role of PI‐PLC β1/PKC‐α signaling in erythropoiesis but also lead to a better comprehension of the lenalidomide effect on del(5q) MDS and pave the way to innovative, targeted therapies.—Poli, A., Ratti, S., Finelli, C., Mongiorgi, S., Clissa, C., Lonetti, A., Cappellini, A., Catozzi, A., Barraco, M., Suh, P.‐G., Manzoli, L., McCubrey, J. A., Cocco, L., Follo, M. Y. Nuclear translocation of PKC‐α is associated with cell cycle arrest and erythroid differentiation in myelodysplastic syndromes (MDSs). FASEB J. 32, 681–692 (2018). www.fasebj.org